Visibility as a factor in the copepod-planktivorous fish relationship - Rudi Strickler, J.; Udvadia, Ava J.; Marino, John; Radabaugh, Nick; Ziarek, Josh; Nihongi, Ai (Scientia Marina, 2005)
The question we treat in this contribution is whether or not planktivorous fish can use the motion pattern of planktonic copepods to distinguish these animals from other suspended particles in the water. A targeted overview of the predator-prey relationship is followed by a first report of experiments performed in our laboratory where fish selected between two virtual targets on a TV screen, each target showing a different swimming pattern. The results suggest that fish can perceive temporal visual patterns and select their preferred target after two to ten seconds observing the two moving targets. Implications of these preliminary results are discussed and hypotheses for further research formulated.